The HDAC2-SP1 axis orchestrates protumor macrophage polarization - Zheng, Xiang; Sarode, Poonam; Weigert, Andreas; Turkowski, Kati; Chelladurai, Prakash; Günther, Stefan; Kuenne, Carsten; Winter, Hauke; Stenzinger, Albrecht; Reu, Simone; Grimminger, Friedrich; Stiewe, Thorsten; et al. (Cancer research, 2023)
Tumor-associated macrophages (TAM), including antitumor M1-like TAMs and protumor M2-like TAMs, are transcriptionally dynamic innate immune cells with diverse roles in lung cancer development. Epigenetic regulators are key in controlling macrophage fate in the heterogeneous tumor microenvironment. Here, we demonstrate that the spatial proximity of HDAC2-overexpressing M2-like TAMs to tumor cells significantly correlates with poor overall survival of lung cancer patients. Suppression of HDAC2 in TAMs altered macrophage phenotype, migration, and signaling pathways related to interleukins, chemokines, cytokines, and T-cell activation. In coculture systems of TAMs and cancer cells, suppressing HDAC2 in TAMs resulted in reduced proliferation and migration, increased apoptosis of cancer cell lines and primary lung cancer cells, and attenuated endothelial cell tube formation. HDAC2 regulated the M2-like TAM phenotype via acetylation of histone H3 and transcription factor SP1. Myeloid cell-specific deletion of Hdac2 and pharmacologic inhibition of class I HDACs in four different murine lung cancer models induced the switch from M2-like to M1-like TAMs, altered infiltration of CD4+ and CD8+ T cells, and reduced tumor growth and angiogenesis. TAM-specific HDAC2 expression may provide a biomarker for lung cancer stratification and a target for developing improved therapeutic approaches.HDAC2 inhibition reverses the protumor phenotype of macrophages mediated by epigenetic modulation induced by the HDAC2-SP1 axis, indicating a therapeutic option to modify the immunosuppressive tumor microenvironment.
Veröffentlicht: 14. Juli 2023
Gesehen am 06.10.2023